Perhexiline maleate toxicity on human liver cell lines. Issue 11 (November 1980) - Le Gall, J Y; Guillouzo, A; Glaise, D; Deugnier, Y; Messner, M; Bourel, M
Abstract : When added to the culture medium of human liver cell lines, perhexiline maleate induced formation of numerous myeloid bodies containing unicentric or multicentric smooth membranes within a few days. The nine lysosomal enzyme activities studied, except for beta-galactosidase which decreased, remained unchanged. These results indicate that on cultured human liver cells perhexiline maleate has an effect similar to that described on hepatocytes of some patients treated with this drug and suggest that myeloid body formation is not due to impairment of lysosomal enzyme activities.